2018
DOI: 10.1155/2018/1965807
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary Lifestyle and Nonspecific Low Back Pain in Medical Personnel in North-East Poland

Abstract: Introduction The sedentary lifestyle is defined as prolonged sitting both at work and during leisure time, with energy expenditures of below 600 MET · min/week. The sedentary lifestyle is a well-known predictor of obesity and other components of the metabolic syndrome. The influence of the sedentary lifestyle and associated factors on nsLBP is still being discussed. Aim The aim of this study was to assess the influence of a sedentary lifestyle and its associated metabolic predictors on the prevalence of nsLBP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
1
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 32 publications
2
62
1
15
Order By: Relevance
“…The sedentary lifestyles often predominate in older age which can cause several health issues including LBP. Physicians and health-promoting authorities have a responsibility to promote physical activity amongst older people [11]. Even though obesity is often correlated with low physical activity in LBP patients, surprisingly we could not find any relation between these variables [18].…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The sedentary lifestyles often predominate in older age which can cause several health issues including LBP. Physicians and health-promoting authorities have a responsibility to promote physical activity amongst older people [11]. Even though obesity is often correlated with low physical activity in LBP patients, surprisingly we could not find any relation between these variables [18].…”
Section: Discussioncontrasting
confidence: 63%
“…According to our data RAPA 1, most of the patients with back pain were sedentary 117 (32.5%) and underactive 176 (48.9%). Citko et al concluded similar results in their study and found that the sedentary lifestyle significantly increased the incidence of recurring LBP [11]. It is evident that a person who sits too much was more likely to experience back pain [12].…”
Section: Discussionsupporting
confidence: 58%
“…ratownicy ze stażem pracy do 5 lat odczuwali ból umiarkowany (4,02 pkt), a pracujący w zawodzie powyżej 5 lat odczuwali nawet silny ból wg skali VAS (5,68 pkt) [13]. Wpływ stażu pracy na nasilanie się dolegliwości bólowych kręgosłupa odnotowali także inni autorzy badający różny personel medyczny [16,17].…”
unclassified
“…Wyniki te zasługują na szczególną uwagę, gdyż wcześniej nie rejestrowano w bazie danych publikacji oceniających wyłącznie ratowników pod kątem niepełnosprawności ze względu na ZBK. Dotychczas kwestionariusz Oswestry był wykorzystywany do oceny niesprawności innych grup pracowników służby zdrowia, takich jak: lekarze, pielęgniarki, fizjoterapeuci i sanitariusze, również narażonych na występowanie ZBK w związku z wykonywaną pracą -WRMSDs [16][17][18][19]. Badając różny personel medyczny, w tym lekarzy, pielęgniarki i sanitariuszy pakistańskiego szpitala, Tanzil i wsp.…”
unclassified
“…A sedentary lifestyle, which is more common in countries with a high human development index, shows a significantly increased incidence of recurring back pain [6][7][8]. The reduced physical activity, which characterizes the sedentary lifestyle, leads to a reduction of muscle power and strength in particular of the trunk [9].…”
Section: Introductionmentioning
confidence: 99%